PENGARUH INOVASI LAYANAN DAN DIGITAL MARKETING TERHADAP KINERJA PEMASARAN PADA PARTNER PERCETAKAN - Dzulfikri Azis Muthalib (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to analyze the effect of service innovation and digital marketing on marketing performance among printing business partners. This research uses a quantitative approach with an explanatory research design. The population consists of printing partners affiliated with a printing enterprise, with a sample of 90 respondents determined based on the number of research indicators multiplied by five, using a saturated/purposive sampling technique. Data were collected through questionnaires using a five-point Likert scale and analyzed using multiple linear regression with the assistance of SPSS software. The results show that service innovation and digital marketing simultaneously have a positive and significant effect on marketing performance. Partially, service innovation has a positive and significant effect on marketing performance, while digital marketing has a positive and significant effect and is the most dominant variable. These findings suggest that continuous service innovation combined with effective digital marketing practices are key drivers of marketing performance among printing partners.